Attitudes and Behaviours Regarding COVID‐19 Mitigation Strategies in Australians With an Underlying Health Condition: A Cross‐Sectional Study - Sze‐Ee Soh; Darshini Ayton; Amelia Bevins; Helen Skouteris; Mallory Trent; Raina MacIntyre (Wiley, 2024)
ABSTRACT Background Public health strategies have focused on preventing and slowing the transmission of COVID‐19 by promoting the uptake of mitigation strategies. However, little is known about the uptake of these strategies in the presence of underlying health conditions. Objectives To describe the attitudes and behaviours of a sample of Australians towards COVID‐19 mitigation strategies, and determine if uptake of these strategies differed across different health conditions. Design Cross‐sectional study. Setting and Participants National survey of Australian residents over 18 years. Main Outcome Measures A purpose‐built survey was used to collect participants' attitudes and behaviours towards COVID‐19 mitigation strategies. Results Over half (53%) of the 2867 participants (99% completion rate) reported having one or more comorbidities. The most commonly self‐reported health condition was cardiometabolic conditions (28%). Most participants disagreed that masks were no longer needed (74%) and wanted the 5‐day isolation mandate (66%). More than one‐third would like masks to be mandated for indoor spaces (38%) and 25% avoided going to hospitals. Participants with allergies (OR 1.37; 95% CI 1.14, 1.65), cardiometabolic (OR 1.49; 95% CI 1.23, 1.79), respiratory (OR 1.32; 95% CI 1.07, 1.62) and neurological (OR 1.62; 95% CI 1.12, 2.32) conditions were more likely to avoid using public transport compared to those without. In contrast, participants with underlying mental health conditions were less likely to use N95/P2 facemasks in public spaces (OR 0.46; 95% CI 0.25, 0.87) compared to those without. Conclusions A substantial proportion of Australians continued to adopt COVID‐19 mitigation measures or expressed a desire for more mitigations, including mandatory isolation for COVID‐19, despite the lack of mandates. People with an underlying health condition who represent more than half of all adults appear to be more careful with mitigations to avoid COVID‐19. Patient or Public Contribution Members of the public were invited to participate in a soft launch of the survey between 4th and 5th January 2023 to test flow and functionality, and to allow the final wording of survey questions to be refined as required.